2014
DOI: 10.1111/cgf.12396
|View full text |Cite
|
Sign up to set email alerts
|

Visual Analysis of Time‐Series Similarities for Anomaly Detection in Sensor Networks

Abstract: We present a system to analyze time-series data in sensor networks. Our

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 31 publications
1
38
0
3
Order By: Relevance
“…Therefore, we picked several colormaps that provide a reasonable compromise between tasks ER2, ER3, SR2 presented by Bernard et al [BSM∗15, Table 3]. For the example in Figure 10, we chose the Mittelstädt et al colormap [SBM∗14]. In the implemented prototype we allow the user to choose between the Bremm et al regular and stretched [BLBS11], TeulingFig3NoWhitening [TSS11], and the presented Mittelstädt et al colormaps.…”
Section: Use Casementioning
confidence: 99%
“…Therefore, we picked several colormaps that provide a reasonable compromise between tasks ER2, ER3, SR2 presented by Bernard et al [BSM∗15, Table 3]. For the example in Figure 10, we chose the Mittelstädt et al colormap [SBM∗14]. In the implemented prototype we allow the user to choose between the Bremm et al regular and stretched [BLBS11], TeulingFig3NoWhitening [TSS11], and the presented Mittelstädt et al colormaps.…”
Section: Use Casementioning
confidence: 99%
“…The SA‐related analytical tasks can be synthesized into the following main types: SA1 :Summarize information from heterogeneous streaming data sources for identifying causal relationships behind the changing patterns. SA2 :Take domain knowledge into account and let analysts explore dynamic what‐if scenarios. Based on our survey, we found that very few papers (with the exception of [Erb12, FK14, MJR*11, SBM*14]) address situational awareness scenarios. In Figure , we see one such example where interactive feature selection is used for summarizing and reasoning purposes.…”
Section: Problem Characterizationmentioning
confidence: 99%
“…The data set is typically multivariate. Related work is for example performed by Steiger et al [45], who described zoomable glyphs. Viewed from a distance, glyphs are recognizable in shape in color; zooming in brings out the information captured by each glyph at detail level.…”
Section: Status Update Viewmentioning
confidence: 99%